Clonal Diversity of Metallo-β-Lactamase-Possessing Pseudomonas aeruginosa in Geographically Diverse Regions of Japan - Kimura, Soichiro (American Society for Microbiology, 2005)
The aim of this study was to determine the distribution of metallo-β-lactamase-producing Pseudomonas aeruginosa in Japan and to investigate the molecular characteristics of resistance gene cassettes including the gene encoding this enzyme. A total of 594 nonduplicate strains of P. aeruginosa isolated from 60 hospitals throughout Japan in 2002 were evaluated. This study indicated that although the prevalence of imipenem-resistant P. aeruginosa has not increased compared to that found in previous studies, clonal distribution of the same strain across Japan is evident.